PIN1 Modulates Huntingtin Levels and Aggregate Accumulation: An In vitro Model - Carnemolla, Alisia; Michelazzi, Silvia; Agostoni, Elena (Frontiers in Cellular Neuroscience, 2017)
Huntington’s disease (HD) is a dominantly inherited neurodegenerative disorder characterized by a polyglutamine expansion within the N-terminal region of huntingtin protein (HTT). Cellular mechanisms promoting mutant huntingtin (mHTT) clearance are of great interest in HD pathology as they can lower the level of the mutant protein and its toxic aggregated species, thus affecting disease onset and progression. We have previously shown that the prolyl-isomerase PIN1 represents a promising negative regulator of mHTT aggregate accumulation using a genetically precise HD mouse model, namely HdhQ111 mice. Therefore, the current study aims at underpinning the mechanism by which PIN1 affects huntingtin’s aggregates. We found that PIN1 overexpression led to a reduction of mHTT aggregates in HEK293 cells, and that this could be linked to a negative regulation of mHTT half-life by PIN1. Furthermore, we show that PIN1 has the ability to stimulate the proteasome presenting evidence of a mechanism regulating this phenomenon. Our findings provide a rationale for future investigation into PIN1 with the potential for the development of novel therapeutic strategies.